Ultrahigh damping capacity achieved by modulating R phase in Ti49.2Ni50.8 shape memory alloy wires. (1st July 2020) - Jin, Mingjiang; Song, Yuanwei; Wang, Xiaodong; Chen, Peng; Pang, Guobo; Jin, Xuejun
Abstract: An ultrahigh damping capacity with internal friction close to 0.35 was detected over a large temperature range of 75  °C (from -40 to 35  °C) in Ti49.2 Ni50.8 shape memory wires by adjusting the B2→R phase transformation through a low-temperature aging treatment. Microstructural analysis showed that the excellent damping performance is attributed to high-density nanodomains in the R phase, which are induced by short-range Ni segregation. These results are expected to further expand capacity for designing damping microstructure. Graphical abstract: Image, graphical abstract